Den danske kirke i Sverige 1943-45 - Saltorp, Birgitte (Kirkehistoriske Samlinger, 1989)
From 1943-45 approx. 18,200 Danes fled the occupied Denmark, among these were 15 parsons of the Danish Lutheran Church. Poul Borchsenius, the first of the fifteen, at once (December 1943) started work among his countrymen, Christians and Jews alike, supported by Swedish government funds designated the exiled Danes. The Danish Church in Sweden had no formal contact with Denmark so the parsons handled problems as they occurred - Borchsenius even offended against paragraph 3 of the Danish Constitution when he arranged that the »exile state« should hire the only Jewish rabbi who had escaped to Sweden. Also, the church had no formal leader though there seems to have been some dispute between Borchsenius and some of the other parsons on the subject. The parsons each had their »district« of Sweden and rarey met. Klarabergsgatan in Stockholm housed the central church office, duties seemingly being to register baptisms etc. and to arrange contact between lay and clergy Danes. The work included services, baptisms, graveside ceremonies, and the blessing of newlyweds (the parsons were not allowed to perform the actual wedding ceremony). Under Swedish supervision a church bulletin was made, editor was a student of divinity Johannes Dragsdahl whose letters to underground friends in Denmark show the conflict between the »church at war« and the neutral Swedish mind. By the request of Commander-in-Chief K. Knudtzon army chaplains were designated the batallions of The Danish Brigade from spring 1944, rather uniquely the chaplains were allowed and trained to carry arms. Having been active against the Germans in Denmark the parsons’ political involvement was obvious and may be noted in the few still extant sermons and lectures.